PELATIHAN LAPORAN KEUANGAN SEDERHANA DALAM USAHA UKM KERIPIK BAWANG DAYAK DI PALANGKA RAYA - Hansly Hansly; Peridawaty Peridawaty (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to improve the understanding and skills of Small and Medium Enterprises (SMEs) of Dayak Onion Chips in Palangka Raya in preparing simple financial reports. The main problems faced by SMEs are the lack of orderly recording of business transactions, the mixing of personal and business finances, and the lack of understanding in calculating production costs, profit and loss, and cash flow. This training is carried out through counseling methods, transaction recording practices, simulations of simple income statements, and direct assistance to business actors. The training materials are tailored to the needs of SMEs, especially local processed businesses based on Dayak onions which have economic potential as a typical product of Central Kalimantan. The results of the activity showed that participants were able to understand the importance of financial recording, compile daily cash books, calculate the cost of production, separate personal and business finances, and make simple income statements. This activity is expected to increase the managerial capacity of SMEs, strengthen business competitiveness, and support the sustainability of the Dayak Onion Chips business in Palangka Raya.